Enabling change in forest tenure: Policy and law for gender equality: Training handbook - Jhaveri, Nayna J. (Center for International Forestry Research, 2021)
This training handbook accompanies the publication, Forest tenure pathways to gender equality: A practitioner’s guide. The approximately six-hour course develops a compelling strategic approach and action plan for gender-responsive forest tenure reform. Part of this process involves carrying out a policy and legal gap analysis of forest tenure regulatory frameworks. This work is aligned with step two of the three-step change pathway for gender equality in the Practitioner’s guide: Strategize. The content of the handbook and its handouts are illustrative and can be tailored to different training requirements. For example, if the course is used for government staff or members of a non-governmental organization, the content and exercises can be adjusted to suit the knowledge background and interests of participants.